PHYSICAL ACTIVITY IN THE MAINTENANCE OF THE QUALITY OF LIFE OF ELDERLY PEOPLE WITH OSTEOPOROSIS: A NARRATIVE LITERATURE REVIEW - Luís Lopes Gomes de Siqueira, André; Laís Araújo da Silva, Carmem; Cristina Rolim Baggio, Maria (Health and Society, 2023)
Osteoporosis is considered one of the most common chronic degenerative diseases in the elderly, and is currently recognized as a major public health problem in the world, characterized by reduced bone mass and deterioration of tissue microarchitecture, which weakens the bones making them more fragile and susceptible to fractures. Physical activity influences the maintenance of normal bone activities, being recommended in the treatment of osteoporosis, besides providing several benefits, both physical, psychological, and social, which are of great relevance for the promotion and maintenance of health and quality of life. Therefore, the interest in the subject of this article arises, which aims to verify in the scientific literature the influence of physical exercise in the treatment of osteoporosis in elders and the importance of the practice for the maintenance of life quality, as well as to identify which types of physical activities are more appropriate for the treatment of osteoporosis in seniors. For this study, a narrative literature review was carried out using the electronic databases SciELO, PubMed, and LILACS, with the following descriptors in Portuguese: osteoporose, idosos, atividade física e qualidade de vida; and in English: osteoporosis, physical activity, elderly, and quality of life. Regarding quality of life and physical aspects such as strength and balance, all the studies reported improvement in the quality of life and physical indicators of the participants, except for one. The adherence to a routine of physical exercises in the elderly population with osteoporosis proved to be essential for the maintenance of health and well being, acting both in the treatment and prevention of this pathology. The greatest benefits were evidenced with the association of resistance training to balance training, aerobic exercises, mobility, and stretching.